2016
DOI: 10.1039/c6ee02016j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of CH3NH3PbI3 perovskite into NH3 and CH3I gases observed by coupled thermogravimetry–mass spectrometry analysis

Abstract: Thermal gravimetric and differential thermal analysis (TG-DTA) coupled with quadrupole mass spectrometry (MS) and first principles calculations were employed to elucidate the chemical nature of released gases during the thermal decomposition of CH3NH3PbI3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
609
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 684 publications
(631 citation statements)
references
References 21 publications
16
609
2
4
Order By: Relevance
“…Juarez-Perez et al reported the chemical decomposition of MAPbI 3 using thermogravimetric analysis and differential thermal analysis, and found that decomposition to CH 3 I, NH 3 , and PbI 2 started at 294 °C. [160] These studies imply that the surface of the MAPbI 3 film decomposed to PbI 2 , CH 3 I, and NH 3 after being heated at >100 °C, and only PbI 2 remained on the surface after CH 3 I and NH 3 evaporated. Decomposition of CH 3 NH 3 + is more likely to happen during the rapid formation of MAPbI 3 from precursor materials.…”
Section: Thermally Induced Chemical Decompositionmentioning
confidence: 99%
“…Juarez-Perez et al reported the chemical decomposition of MAPbI 3 using thermogravimetric analysis and differential thermal analysis, and found that decomposition to CH 3 I, NH 3 , and PbI 2 started at 294 °C. [160] These studies imply that the surface of the MAPbI 3 film decomposed to PbI 2 , CH 3 I, and NH 3 after being heated at >100 °C, and only PbI 2 remained on the surface after CH 3 I and NH 3 evaporated. Decomposition of CH 3 NH 3 + is more likely to happen during the rapid formation of MAPbI 3 from precursor materials.…”
Section: Thermally Induced Chemical Decompositionmentioning
confidence: 99%
“…These results indicate that the tetragonal phase was transformed into the cubic phase during heat stress application, and the onset temperature of thermal degradation was estimated at 100 °C. The cubic phase of MAPbI 3 perovskite started to decompose while going through the intermediate phase, leaving only PbI 2 once CH 3 I and NH 3 evaporated 38 . In addition to the rapid thermal degradation that took place when the sample was heated for a short time at 100 °C, long-term application (1 h) of heat stress also led to thermal decomposition at lower temperature of 80 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Juarez-Perez et al . reported the thermal decomposition of MAPbI 3 through thermogravimetric analysis and differential thermal analysis (TG-DTA) coupled with quadrupole mass spectrometry (MS), and reported that MAPbI 3 started to decompose to CH 3 I, NH 3 and PbI 2 at 294 °C 38 . These results indicate that the surface of the MAPbI 3 film decomposed to PbI 2 , CH 3 I, and NH 3 after being heated at >100 °C, and only PbI 2 remained on the surface after CH 3 I and NH 3 evaporated.…”
Section: Resultsmentioning
confidence: 99%
“…While Sample E contains 16.8% Cs + in bulk and 52.8% Cs + at the film surface. Although it has been reported that 15% Cs + in Cs 0.15 FA 0.85 PbI 3 PSC is thermally stable, [33] such a high Cs + ratio at perovskite surface can lead to obvious phase Inset of (b) shows the enlarged spectra by five times, which is assigned to Pb 0 impurity. Ratios between g) Pb 2+ to I − and h) Cs + to I − calculated from XPS, UV-vis, XRD, and PL.…”
Section: Stability Of the Mixed Cs X Fa 1−x Pbi 3 Perovskite Solar Cementioning
confidence: 99%
“…[24] For example, the most widely investigated methylammonium (CH 3 NH 3 + or MA) lead iodide (MAPbI 3 ) is reported to undergo a phase transition at 54-57 °C [30,31] and degrade at temperature over 85 °C, [32] suggesting its poor thermal stability. [33] Among other perovskite materials, formamidinium (NH 2 CHNH 2 + or FA) lead iodide (FAPbI 3 ) possesses better thermal stability compared to MAPbI 3 and relatively high device performance among various types of perovskites. [34] However, an obvious drawback is its phase stability in the perovskite structure.…”
Section: Introductionmentioning
confidence: 99%